Analisis Peluang dan Ancaman Perdagangan Produk Kerajinan Tangan Tradisional serta Upaya Perlindungan Hak Kekayaan Intelektual: Studi Kasus Indonesia dan Australia - Nurhikmah Fitria; Daspar (CV. ITTC INDONESIA, 2025)
The international trade of traditional handicraft products continues to grow alongside the increasing global interest in culturally rich and sustainable goods. This study analyzes the opportunities and challenges of trading Indonesian traditional handicrafts in the Australian market and highlights the importance of Intellectual Property Rights (IPR) protection in preserving the authenticity and economic value of these products. The findings reveal that although the Australian market presents significant potential, issues such as design counterfeiting, cultural exploitation, and limited legal protection remain critical obstacles. Therefore, strategies such as community-based collective protection, legal education for artisans, and cross-country collaboration are essential to strengthen traditional cultural protection systems within the global trade framework.